2012
DOI: 10.1590/1677-553820133806728
|View full text |Cite
|
Sign up to set email alerts
|

Penile Cancer Disparities in Puerto Rican Men as compared to the United States Population

Abstract: Purpose This study compares incidence and mortality of penile cancer in Puerto Rico (PR) with other racial/ethnic groups in the United States (US) and evaluates the extent in which socioeconomic position index (SEP) or its components influence incidence and mortality in PR. Materials and Methods Age-standardized rates were calculated for incidence and mortality based on data from the PR Cancer Registry and the US National Cancer Institute’s Surveillance, Epidemiology and End Results program, using the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…20,27 Several intervention strategies may be effective in increasing knowledge and uptake of screening guidelines. Two recent reviews described successful intervention strategies for Hispanic CRC screening, 28,29 including the use of bilingual navigators who are members of the targeted community, educational interventions aimed at providers, and culturally sensitive printed materials. 29,30 However, even identifying unscreened individuals may be difficult since Hispanics are less likely to have a regular source of medical care.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
“…20,27 Several intervention strategies may be effective in increasing knowledge and uptake of screening guidelines. Two recent reviews described successful intervention strategies for Hispanic CRC screening, 28,29 including the use of bilingual navigators who are members of the targeted community, educational interventions aimed at providers, and culturally sensitive printed materials. 29,30 However, even identifying unscreened individuals may be difficult since Hispanics are less likely to have a regular source of medical care.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
“…Therefore, there is a need to consider conducting future qualitative studies targeting parents and children from different age-gender subgroups. Specifically, future efforts should focus among young men, where a wide area of research in Puerto Rico has shown a higher burden of HPV infection as well as HPV-related cancers (Colón-López et al 2015; Colón-López et al 2014; Colón-López et al 2013; Colón-López et al 2012; Colón-López et al 2010). …”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…1,2 Among men, several studies have reported that oncogenic (high-risk) HPV types may be responsible for HPV-related cancers such as oropharyngeal, anal, and penile cancer. 3,4 Studies in Puerto Rico (PR) have reported an increased risk of penile cancer in men compared with other racial/ethnic groups in the United States (U.S.), 5 as well as an increased incidence trend of anal cancer of 26.9%, comparing the period of 2001–2004 to that of 1992–1996. 6 …”
mentioning
confidence: 99%